2015
DOI: 10.1186/s12931-015-0247-x
|View full text |Cite
|
Sign up to set email alerts
|

Altered protease and antiprotease balance during a COPD exacerbation contributes to mucus obstruction

Abstract: BackgroundProteases have been shown to degrade airway mucin proteins and to damage the epithelium impairing mucociliary clearance. There are increased proteases in the COPD airway but changes in protease-antiprotease balance and mucin degradation have not been investigated during the course of a COPD exacerbation. We hypothesized that increased protease levels would lead to mucin degradation in acute COPD exacerbations.MethodsWe measured neutrophil elastase (NE) and alpha 1 protease inhibitor (A1-PI) levels us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 30 publications
0
21
0
1
Order By: Relevance
“…Comorbidity of COPD was further proved to be an independent risk factor for presenting initial respiratory symptoms. To some extent, this can be explained by the hypothesis that tumors may be more easily to obstruct the otherwise narrowed airways with hyper-mucus secretion in patients with COPD 22 and thus cause initial respiratory symptoms early.…”
Section: Discussionmentioning
confidence: 99%
“…Comorbidity of COPD was further proved to be an independent risk factor for presenting initial respiratory symptoms. To some extent, this can be explained by the hypothesis that tumors may be more easily to obstruct the otherwise narrowed airways with hyper-mucus secretion in patients with COPD 22 and thus cause initial respiratory symptoms early.…”
Section: Discussionmentioning
confidence: 99%
“…1,3 Roy and colleagues showed that Muc5b, but not Muc5ac, was required for airway defense and that the decrease of Muc5b could hamper mucus clearance. 19 Additionally, publications have stated that the levels of MUC5B in BALF and sputum were increased in COPD patients, [32][33][34] while carbocisteine could balance fucosylated and sialylated sugar chains, 13 normalize the viscous property of mucus 12 and reduce MUC5AC expression. We speculated that the decrease of Muc5b might have played an important role in COPD pathogenesis and carbocisteine might reduce the expression of Muc5b in COPD mice model.…”
Section: Discussionmentioning
confidence: 99%
“…Cysteine-rich secretory, or gelatinous secretory mucin gives mucus its characteristic viscoelasticity and this property is critical to clearance of xenobiotics by ciliated cells. MUC5AC and MUC5B are the most important and abundant mucins, comprising about 75% of mucins [ 4 , 37 ]. These mucins are abundantly expressed in normal and stressed states.…”
Section: The Biological Characteristics Of Mucinsmentioning
confidence: 99%